Axial compressive capacity of RC square columns strengthened by prestressed CFRP with RPC pads. (15th June 2020) - Wang, Qiang; lu, Chunling; Zhu, Wanxu; Fu, Feng; Qian, Kai
Abstract: In this paper, a new technique to strengthen RC square columns using prestressed CFRP patched by ractive powder concrete (RPC) pad is developed. Fifteen RC square columns strengthened using this new technique were tested under axial compression loads. The influence of the level of prestress force, the number of wrapping layers and the strengthening process on the strengthening effect of this new technique was investigated. The improvement of axial compressive capacities and failure modes of the columns were studied. The results show that: this new technique provides better strengthening to the concrete columns with a fast strengthening process. The axial compression capacity of RC columns increases up to 80%. It is also found that, increasing the prestress can also improve the performance of the columns under normal working condition. A formula to predict the axial compression capacity of the columns is developed in this paper, which can accurately predict the axial compressive strength of the concrete columns strengthened by this new technique.